Peran Agen Perubahan dalam Pengembangan SDN 34 Kuranji Padang - Fadhlya Hidayattul Alimun (GLOBAL SCIENTS PUBLISHER, 2025)
Change agents play a strategic role in driving educational transformation, particularly in primary schools facing the dual challenges of adapting to national policies and responding to dynamic social contexts. This qualitative descriptive case study examines the role of change agents in the development of SDN 34 Kuranji Padang, focusing on participatory leadership strategies, internal external collaboration, resource utilization, and cultural strengthening. Data were collected through participatory observation, semi-structured interviews, and analysis of official school documents. The data were analyzed using the Miles and Huberman interactive model consisting of data reduction, display, and verification. The findings reveal that change agents at SDN 34 Kuranji Padang work collectively through collaboration among school principals, teachers, staff, parents, and the community. The principal acts as a catalyst and strategic leader, teachers serve as facilitators and problem solvers, while parents and the community function as cultural and resource supporters. Successful change is supported by teacher training funded through BOS Kinerja, integration of local cultural activities, and active parental involvement. This study contributes a conceptual model of Collective Change Agents in Primary Schools, emphasizing participatory leadership, capacity building, strategic resource mobilization, and local cultural integration as the main pillars of sustainable primary school development.